Intrinsic Functional Plasticity of the Thalamocortical System in Minimally Disabled Patients with Relapsing-Remitting Multiple Sclerosis - Zhou, Fuqing; Gong, Honghan; Chen, Qi; Wang, Bo; Peng, Yan; Zhuang, Ying; Zee, Chi-shing (Frontiers in Human Neuroscience, 2016)
The thalamus plays a crucial role in sensorimotor, cognitive and attentional circuit functions. Disruptions in thalamic connectivity are believed to underlie the symptoms of multiple sclerosis (MS). Therefore, assessing thalamocortical structural connectivity (SC) and functional connectivity (FC) may provide new insights into the mechanism of intrinsic functional plasticity in a large-scale neural network. We used resting-state FC measurement and diffusion tensor imaging probabilistic tractography to study the functional and structural integrity of the thalamocortical system in patients with relapsing-remitting MS (RRMS) and matched healthy controls. In the thalamocortical connections of RRMS patients, we found lesion load-related regional FC in the right temporal pole, which reflected compensatory hyperconnectivity related to lesion-related demyelination. We also found significant correlations between increased diffusivity and slowed cognitive processing (PASAT) or the impact of fatigue (MFIS-5), as well as between connective fiber loss and disease duration. Taken together, the evidence from SC and FC analysis of the thalamocortical system suggests that minimally disabled RRMS patients exhibit a dissociated SC-FC pattern and limited regional functional plasticity to compensate for the chronic demyelination-related loss of long-distance SC. These results also provide further evidence supporting the notion that MS is a disorder of anatomical disconnection.